Preparation method of breathable underwater self-adhesion myoelectricity sensing fabric
By combining graphene oxide with water-based polyurethane and using a specific process flow to prepare breathable electromyosensitivity textiles, the shortcomings of existing materials in water resistance and heat resistance are solved, and self-adhesion underwater is achieved and the functions of efficient sensing have expanded their application prospects in health detection and sensor components.
Patent Information
- Application Number
- CN202411290145.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-02-18
Smart Images

Figure CN119465664A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene, polyurethane and wet adhesive applications, and specifically refers to a method for preparing a breathable underwater self-adhesive electromyographic sensing fabric. Background Art
[0002] Graphene is a two-dimensional flat material composed of a single layer of carbon atoms tightly arranged in a sp2 orbital hybridization mode. Its structure is similar to a honeycomb. This material has attracted much attention for its many cutting-edge properties, including tough mechanical strength, outstanding heat transfer properties, excellent current conduction capacity, huge specific surface area and excellent optical properties. Despite this, graphene is not very hydrophilic or lipophilic, has low chemical activity, and is prone to strong adhesion when stacked. These factors make it easy to agglomerate when mixed with other polymer materials. Such aggregation may reduce its overall performance as a composite. Through a two-step method, graphene oxide with a composite hydroxyl carboxyl group is used to compound with a homemade viscous water-based polyurethane, so that the electrical properties, hydrophobicity and heat resistance of the water-intolerant graphene oxide and water-based polyurethane are transformed.
[0003] The solvent-based polyurethane adhesives currently in the market contain volatile organic solvents that are potentially ignitable and toxic, which can cause environmental damage and threaten public safety during use. With the increasing global awareness of ecological protection and the tightening of environmental protection regulations, the use of such polyurethane adhesives has been restricted. At the same time, non-toxic and environmentally friendly water-based polyurethane adhesives have attracted attention. This water-based polyurethane uses water instead of organic solvents as a dispersion medium. It is non-toxic, non-flammable, and more environmentally friendly. It also has the properties of plastics and rubber, and has excellent wear resistance and adhesion. It is widely used in a variety of coatings, adhesives, surfactants and other industries, and has huge market potential. Although water-based polyurethane adhesives inherit many advantages of solvent-based adhesives, they are insufficient in water resistance and heat resistance after the introduction of hydrophilic groups, which limits their scope of application. In addition, with the continuous development of science and technology, higher requirements are placed on the physical and mechanical properties of materials. Therefore, in order to enhance the overall performance of water-based polyurethane and expand its application, it is necessary to further modify and study it.
[0004] In response to the above problems, this new technology introduces a process for preparing myoelectric sensing fabrics with breathable and self-adhesive characteristics in water environments. In this process, sticky water-soluble polyurethane is combined with graphene oxide and then coated on the surface of the sensing fabric, giving it excellent wet adhesion. This fabric can not only achieve strain sensing, but also has good adhesion to biological tissues, and can be used to prepare efficient human health detection devices and self-adhesive sensor devices. Compared with existing graphene and polyurethane composites, this fabric material has more superior performance and broad application prospects. Summary of the invention
[0005] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a method for preparing a breathable, underwater self-adhesive electromyographic sensing fabric. The fabric not only has a simple preparation process and is green and non-toxic, but also does not require pretreatment when used, has a wide range of applicable interfaces, and can be used for tissue engineering and sensing materials. Specifically, it is a method for making a breathable and underwater self-adhesive electromyographic sensing textile.
[0006] The technical solution adopted by the present invention is as follows: The present invention proposes a set of process flow for making muscle current sensing fabric with air permeability and self-adhesion in water, including the following detailed production steps:
[0007] Step 1: preparing a G-PU material with high viscosity: using polypropylene glycol, 2,2-dihydroxymethyl propionic acid, isophorone diisocyanate, and dibutyltin dilaurate to prepare a viscous polyurethane solution (AWPU), and using graphene oxide (GO) to react with the above solution to obtain a graphene oxide / polyurethane (G-PU) raw material with underwater viscosity;
[0008] Step 2, preparation of highly elastic and breathable RGO coated fabric: design and use weft-knitted polyester knitted fabric, the polyester yarn is a highly elastic textured yarn, as the base material of the highly elastic knitted fabric; cut it according to the size of 3cm in the warp direction and 0.6-1.0cm in the weft direction, and the polyester fiber and the knitted structure cooperate to obtain highly elastic, breathable and light fabric; use the Hummers method to prepare the GO solution; use a spray gun to evenly spray the GO solution on the above knitted fabric, and then put it in a 60°C oven for drying; use a reducing agent on the dried GO fabric and put it in a 60°C oven for drying to enhance the conductivity of the fabric;
[0009] Step 3, preparation of G-PU / RGO myoelectric fabric: the prepared G-PU raw material is first placed in an ultrasonic instrument for stirring and ultrasonication for 3-5 minutes to enhance dispersibility. After the ultrasonication is completed, a small amount is evenly applied on the RGO fabric in step 2 several times. During the coating process, a small brush is used to evenly apply the surface, and the excess G-PU solution on the surface is removed, leaving only a thin layer of G-PU solution on the surface of the fabric to keep it breathable, and then dried at room temperature;
[0010] Step 4: Construction and data collection of the myoelectric fabric sensing system: Apply the fabric with an initial length of 2 mm to the arm or leg muscles, and connect it to an electromyography tester to record the real-time myoelectric changes of stretching and obtain the corresponding electromyography signal curve.
[0011] Furthermore, the fabric described in step 2 can be a polyester knitted fabric or a nylon knitted fabric, and its transverse density can reach 100-200 wales / 5cm, its longitudinal density can reach 100-200 rows / 5cm, and its surface density can reach 0.01-0.02g / cm 2 .
[0012] Furthermore, the mass ratio of G-PU described in step 3 can be adjusted according to viscosity and mechanical requirements, including but not limited to 0.75wt%-10wt%.
[0013] Preferably, the reducing agent in step 2 includes but is not limited to hydroiodic acid (HI), hydrazine hydrate, etc., and the temperature includes but is not limited to 80-105° C., and the reduction time is 0.5-6 hours.
[0014] Preferably, the stirring, ultrasonic speed and magnetic stirring time in step 3 should be sufficient, and the GO / AWPU should be stationary without phase separation.
[0015] Further, the Hummers method described in step 2 for preparing graphene oxide (GO) comprises the following steps:
[0016] a. Dissolve 1g of sodium nitrate powder in 60ml of 98% concentrated sulfuric acid and pour into an open beaker. Then place in an ice water bath and stir with a magnetic anvil for 15 to 30 minutes.
[0017] b. Slowly add 2 g of graphite powder at a rate of 1 g / min, maintain magnetic stirring (speed 600 rpm / min) and ice water bath for 30 min;
[0018] c. Slowly add 10g potassium permanganate powder to the graphite mixture at a rate of 1g / min and maintain magnetic stirring for 1.5h;
[0019] d. Remove the open beaker from the ice water bath, and allow the reaction system to naturally heat up to about 35°C due to the exothermic intercalation oxidation of graphite by concentrated sulfuric acid. Maintain the magnetic stirring speed at 1000 rpm / min, and maintain the temperature until the color of the solution gradually changes to dark green, and the color on the wall of the beaker shall prevail;
[0020] e. Maintain the self-intercalation oxidation reaction of the reaction system for about 8 hours, so that the color of the mixed solution turns into dark brown;
[0021] f. Pour 90 ml of deionized water in an ice bath steadily and gradually into the mixture containing graphite oxide, and set the stirrer speed to 400 rpm to avoid temperature surges and material splashing caused by strong chemical reactions. When the temperature of the mixed system rises naturally to 85°C, keep the spontaneous heating process for 15 minutes.
[0022] g. Pour 1000 ml of deionized water into the mixture, and then slowly add 30% hydrogen peroxide until a bright yellow color is present.
[0023] h. The solution was allowed to stand and settle, the supernatant was removed, 100 ml of 10% dilute hydrochloric acid was added, and the mixture was stirred evenly by magnetic force for 5 minutes, and the hydrochloric acid ions replaced the sulfate ions. After standing for another 5 hours, the supernatant was removed, and the acid washing step was repeated 3 times, and then the dilute hydrochloric acid was removed by centrifugal washing with deionized water, and the centrifugal washing was repeated until the pH value of the supernatant was greater than 5, and a nearly neutral graphite oxide solution was obtained, which was dark brown in color;
[0024] Furthermore, the preparation of the viscous polyurethane (AWPU) described in step 1 is carried out by the following method:
[0025] Under the condition of a constant temperature oil bath at 60°C, first add 11.25g of polyethylene glycol with a molecular weight of 2000 and 0.6g of 2,2-bis(hydroxymethyl)propionic acid into a three-necked flask with a capacity of 100ml, and use a vacuum pump to evacuate the mixture without turning on the stirring function for 30 minutes; then increase the temperature to 85°C, then pour in 2.7g of isocyanate compound and a drop of dodecyl dibutyltin as a catalyst, and introduce nitrogen while stirring for three hours; during the stirring process, gradually cool down to 75°C and stop nitrogen, add 1ml of acetone and 500ml of 3mg / ml EG / acetone solution, then add 1ml of acetone every half an hour, repeat until a total of 3ml is added, and continue stirring for two hours; then further reduce the temperature to 35°C, add 0.45g of TEA, and stir for 30 minutes; finally, use a separatory funnel to slowly add 35ml of deionized water, remove all equipment and continue stirring at room temperature for one hour.
[0026] Further, the RGO / fabric preparation described in step 2 is carried out by the following method:
[0027] After the GO solution is evenly sprayed on the surface of the fabric with a spray gun, it is placed in an oven at 60°C for drying. The fabric is reduced using a solution such as hydroiodic acid (HI) at a temperature of 95°C for more than 0.5 hours, then rinsed and soaked in deionized water until neutral, and placed in an oven for drying to obtain a fabric coated with GRO on the surface.
[0028] Furthermore, the GO / AWPU composite solution described in step 1 and step 3 is prepared by the following method:
[0029] Add an appropriate amount of GO solution to the AWPU solution, and continue stirring and ultrasonicating to form a laminated coating structure graphene oxide / adhesive polyurethane (GO / AWPU) solution;
[0030] Further, the preparation of RGO / G-PU sensing fabric described in step 3 is carried out by the following method:
[0031] The prepared GO / AWPU solution was evenly and thinly coated on the surface of the prepared RGO fabric in small amounts and multiple times, and the surface was evenly coated with a small brush during the coating process to remove excess G-PU solution on the surface, leaving only a thin layer of G-PU solution on the surface of the fabric. It was dried at room temperature to obtain the RGO / G-PU sensing fabric.
[0032] Preferably, in step 1, the ratio of the 98% concentrated sulfuric acid to sodium nitrate is 60:1, the ratio of the 98% concentrated sulfuric acid to graphite powder is 30:1, and the ratio of potassium permanganate to graphite powder is 5:1.
[0033] Preferably, the ice water bath in step 1 refers to a water bath with a temperature of 2 to 5°C.
[0034] Preferably, the centrifugal washing in step 1 needs to be performed for 4 to 10 rounds.
[0035] The beneficial effects achieved by the present invention using the above structure are as follows:
[0036] 1. The production process of the RGO / G-PU sensing fabric is remarkable in that the conductivity and adhesion of the sensing fabric can be ensured by adjusting the number and amount of coatings. This method can be applied to different types of fabric structures to produce similar structures of different fabrics. In addition, the composition of the composite liquid can be precisely controlled during the preparation process to meet different application requirements.
[0037] 2. The RGO / G-PU preparation method in the present application scheme has many unique characteristics, and the fabric prepared therefrom can be used in a variety of application fields, such as being the core material of a variety of sensors, including pressure sensors, tensile sensors, and chemical sensors. The large-scale and safe production and utilization of RGO / G-PU composite materials will be beneficial to the application and development of graphene composite materials. This method can not only improve the preparation efficiency and quality of composite materials, but also reduce production costs and environmental pollution.
[0038] 3. This technology has excellent breathable and underwater self-adhesive electromyographic sensing fabric preparation effect. Even after 7 days of immersion, it still has strong structural stability, strength, tensile strength and low moisture absorption rate. Its peeling adhesion is also very strong, even reaching 10-20N / cm, and its conductivity is also very strong, reaching 0.01-20S / cm, which is even more stable than the general base material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the preparation flow chart and structural mechanism diagram of the preparation method of RGO / G-PU sensing fabric.
[0040] Figure 2 Infrared spectrum of the prepared RGO / G-PU sensing fabric.
[0041] Figure 3 This is the adhesion test and underwater adhesion conductivity of the prepared RGO / G-PU sensing fabric.
[0042] Figure 4 The prepared RGO / G-PU sensing fabric has good air permeability and is compared with 3M tape after being adhered to the skin for 24 hours.
[0043] Figure 5 This is the test result of adhesion of the prepared RGO / G-PU sensing fabric to glass.
[0044] Figure 6 The test results of human gesture and motion electromyography recognition for the prepared RGO / G-PU sensing fabric.
[0045] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0046] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the embodiments of the present invention, and will further elaborate on the invention through specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are only used as demonstrations and are not intended to limit the boundaries of the patent; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0047] Embodiment 1: A method for preparing a breathable underwater self-adhesive electromyographic sensing fabric proposed by the present invention comprises the following steps:
[0048] Step 1: Dissolve 1g of sodium nitrate powder in 60ml of concentrated sulfuric acid (98%) and place in an open beaker, then stir magnetically in an ice-water bath for 15-30min; slowly add 2g of graphite powder at a rate of 1g / min, maintain magnetic stirring (speed 600rpm / min) and ice-water bath for 30min.
[0049] Step 2: Slowly add 10g of potassium permanganate powder to the graphite mixture at a rate of 1g / min, and maintain magnetic stirring for 1.5h; remove the open beaker from the ice water bath, and allow the reaction system to naturally heat up to about 35°C due to the exothermic intercalation oxidation of graphite by concentrated sulfuric acid, maintain the magnetic stirring speed at 1000rpm / min, and maintain this temperature until the color of the solution gradually changes to dark green, and the color on the wall of the beaker shall prevail; maintain the self-intercalation oxidation reaction of the reaction system for about 8h, and the color of the mixed solution changes to dark brown.
[0050] Step 3: Slowly drip the graphite oxide slurry into the cooled 90ml deionized water to ensure uniform mixing, and set the mixer speed to 400 revolutions per minute to prevent the high temperature and splashing risks caused by the intense chemical reaction. When the mixture is observed to heat up to 85 degrees by itself, maintain the reaction for 15 minutes. Then, add 1000ml of deionized water to the solution, slowly add 30% concentration of hydrogen peroxide until bright yellow appears; then let the mixture stand to allow the impurities to settle, discard the upper clear liquid, and add 100ml of 10% dilute hydrochloric acid to the sediment, and stir with a magnetic stirrer for 5 minutes to fully blend and replace the residual sulfate ions. After standing for five hours, remove the clear liquid again. This process of washing with dilute hydrochloric acid needs to be replicated three times. Next, the residual hydrochloric acid is washed with deionized water by centrifugation, and the centrifugation process is repeated until the pH value of the upper liquid is higher than 5, at which time we can get a graphite oxide solution with a pH value close to neutral and a dark brown color.
[0051] Step 4: In a 100mL three-necked flask, add 11.25g of polyethylene glycol (molecular weight 2000) and 0.6g of 2,2-dihydroxypropionic acid at one time, then put the flask into an oil bath and heat it to 60°C. Start the vacuum pump, vacuum the bottle, and maintain the temperature and state for 30 minutes without stirring. Then raise the temperature to 85°C, quickly add 2.7g of isophorone diisocyanate and a drop of dibutyltin dilaurate as a catalyst into the bottle, fill with nitrogen and start stirring vigorously, and keep this process for 3 hours. When the temperature drops to 75°C, cut off the nitrogen flow, and then add 1mL of acetone and 500mL of 3mg / mL EG (ethylene glycol) and acetone. After that, add 1mL of acetone every half an hour, continue to add until the total amount reaches 3mL, and keep stirring for 2 hours. Then the contents of the flask were cooled to 35°C, 0.45 g of TEA (trimethylamine) was added and stirring continued for 30 minutes. As the last step, 35 mL of deionized water was slowly added dropwise to the system and mixed evenly, and the stirring state was maintained for 1 hour.
[0052] Step 5: Add an appropriate amount of GO solution to the AWPU solution, and continue stirring and ultrasonicating to form a laminated coating structure graphene oxide / adhesive polyurethane (GO / AWPU) solution.
[0053] Embodiment 2: A method for preparing a breathable underwater self-adhesive electromyographic sensing fabric proposed by the present invention comprises the following steps:
[0054] Step 1: Grab 0.5g of sodium nitrate crystals, dissolve them in 30ml of 98% sulfuric acid liquid, then transfer them to an open beaker, and stir them with a magnetic stirring bar in an ice-water bath for 15 to 30 minutes; thereafter, add 1g of carbon powder at a dosing speed of 0.5g per minute, and keep the stirring speed at 600 revolutions per minute, and continue stirring in the ice-water bath for 30 minutes.
[0055] Step 2: Slowly add 5g of potassium permanganate powder to the graphite mixture at a rate of 0.5g / min, and maintain magnetic stirring for 1.5h; remove the open beaker from the ice water bath, and allow the reaction system to naturally heat up to about 35°C due to the exothermic intercalation oxidation of graphite by concentrated sulfuric acid, maintain the magnetic stirring speed at 1000rpm / min, and maintain this temperature until the color of the solution gradually changes to dark green, and the color on the wall of the beaker shall prevail; maintain the self-intercalation oxidation reaction of the reaction system for about 8h, and the color of the mixed solution changes to dark brown.
[0056] Step 3: Slowly and evenly inject the graphite oxide paste into 60ml of deionized cooling water, adjust the stirring speed to 400 revolutions per minute, and avoid the rapid rise in temperature and splashing of the reactants due to the violent chemical reaction; when the temperature of the liquid spontaneously rises to 85°C, keep this state to react chemically for 15 minutes; then pour 500ml of deionized water into it, and slowly add 30% hydrogen peroxide solution until a bright yellow solution is observed; then let the solution stand for precipitation, remove the upper clear liquid, add 60ml of 5% diluted hydrochloric acid, and mix it evenly with a magnetic stirrer at a speed of 400 revolutions per minute for 5 minutes, so that the anions of the hydrochloric acid and the sulfate in the solution undergo a replacement reaction. After letting it stand for 5 hours, discard the clear liquid above, repeat this hydrochloric acid washing step for a total of three times, and then centrifuge with deionized water to remove the remaining diluted hydrochloric acid. The centrifugal washing operation is repeated until the pH value of the obtained supernatant is higher than 5, thus obtaining a nearly neutral, dark brown graphite oxide solution.
[0057] Step 4: In a 60°C oil bath, place 11.25g polypropylene glycol 2000 and 0.6g 2,2-dihydroxymethylpropionic acid in a 100ml three-necked flask, evacuate with an oil pump, and do not stir for 30min; heat to 85°C, add 2.7g isophorone diisocyanate and a drop of dibutyltin dilaurate, introduce N2 and stir for 3 hours; cool to 75°C, stop nitrogen, add 1ml acetone and 500ml 3mg / ml EG / acetone solution, add 1ml acetone every 30min, a total of 3ml and stir for 2 hours; cool to 35°C, add 0.45g TEA, stir for 30 minutes; drop 35ml deionized water and stir for 1h.
[0058] Step 5: After spraying the GO solution evenly on the surface of the fabric with a spray gun, put it in a 60°C oven for drying. Use hydroiodic acid (HI) and other solutions to reduce the fabric at a temperature of 95°C for more than 0.5 hours, then rinse and soak it with deionized water until it is neutral, and put it in an oven to dry to obtain a fabric coated with GRO on the surface.
[0059] Step six, apply the prepared GO / AWPU solution evenly and thinly on the surface of the prepared RGO fabric in small amounts and multiple times, and use a small brush to evenly coat the surface during the coating process, remove excess G-PU solution on the surface, leaving only a thin layer of G-PU solution on the surface of the fabric, and dry at room temperature to obtain RGO / G-PU sensing fabric.
[0060] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A method for preparing a breathable underwater self-adhesive electromyographic sensing fabric, characterized in that: The following steps are involved: Step 1: preparing a G-PU material with high viscosity: using polypropylene glycol, 2,2-dihydroxymethyl propionic acid, isophorone diisocyanate, and dibutyltin dilaurate to prepare a viscous polyurethane solution (AWPU), and using graphene oxide (GO) to react with the above solution to prepare a graphene oxide / polyurethane (G-PU) raw material with underwater viscosity; Step 2: Preparation of highly elastic and breathable RGO coated fabric: Design and use weft-knitted polyester knitted fabric, the polyester yarn is a highly elastic textured yarn, as the base material of the highly elastic knitted fabric; cut it according to the size of 3cm in the warp direction and 0.6-1.0cm in the weft direction, and the polyester fiber and knitted structure cooperate to obtain highly elastic, breathable and light fabric; use the Hummers method to prepare the GO solution; use a spray gun to evenly spray the GO solution on the above knitted fabric, and then put it in a 60℃ oven for drying; use a reducing agent on the dried GO fabric and put it in a 60℃ oven for drying to enhance the conductivity of the fabric; Step 3: Preparation of G-PU / RGO myoelectric fabric: The prepared G-PU raw material is first placed in an ultrasonic instrument for stirring and ultrasonication for 3-5 minutes to enhance dispersibility. After the ultrasonication is completed, a small amount is evenly applied on the RGO fabric in step 2 several times. During the coating process, a small brush is used to evenly apply the surface, and the excess G-PU solution on the surface is removed, leaving only a thin layer of G-PU solution on the surface of the fabric to keep it breathable, and dry at room temperature; Step 4: Construction and data collection of the myoelectric fabric sensing system: Apply the fabric with an initial length of 2 mm to the arm or leg muscles and connect it to an electromyography tester to record the real-time myoelectric changes of stretching and obtain the corresponding electromyography signal curve.
2. The method for preparing a breathable underwater self-adhesive electromyographic sensing fabric according to claim 1, characterized in that: The fabric described in step 2 can be a polyester knitted fabric or a nylon knitted fabric, and its transverse density can reach 100-200 wales / 5cm, the longitudinal density can reach 100-200 rows / 5cm, and the surface density can reach 0.01-0.02g / cm 2 .
3. The method for preparing a breathable underwater self-adhesive electromyographic sensing fabric according to claim 2, characterized in that: The mass ratio of G-PU described in step 3 can be adjusted according to viscosity and mechanical requirements, including but not limited to 0.75wt%-10wt%.
4. The method for preparing a breathable underwater self-adhesive electromyographic sensing fabric according to claim 3, characterized in that: The reducing agent in step 2 includes but is not limited to hydroiodic acid (HI), hydrazine hydrate, etc., and the temperature includes but is not limited to 80-105° C., and the reduction time is 0.5-6 hours.
5. The method for preparing a breathable underwater self-adhesive electromyographic sensing fabric according to claim 4, characterized in that: The stirring, ultrasonic speed and magnetic stirring time described in step 3 must be sufficient, and the GO / AWPU must be stationary without phase separation.
Citation Information
Cited By
Multi-mode life detection and positioning collaboration method for protective underwear for sea battle
CN120932893A
A Collaborative Method for Multimodal Life Detection and Localization of Naval Combat Protective Underwear
CN120932893B
Porous conductive fiber, intelligent fabric and preparation method thereof
CN121161437A